Designing Inherently Photodegradable Cell‐Adhesive Hydrogels for 3D Cell Culture. Issue 16 (10th June 2021) - Rosenfeld, Alisa; Göckler, Tobias; Kuzina, Mariia; Reischl, Markus; Schepers, Ute; Levkin, Pavel A.
Abstract: Light‐based microfabrication techniques constitute an indispensable approach to fabricate tissue assemblies, benefiting from noncontact spatially and temporarily controlled manipulation of soft matter. Light‐triggered degradation of soft materials, such as hydrogels, is important in tissue engineering, bioprinting, and related fields. The photoresponsiveness of hydrogels is generally not intrinsic and requires complex synthetic procedures wherein photoresponsive crosslinking groups are incorporated into the hydrogel. This paper demonstrates a novel biocompatible and inherently photodegradable poly(ethylene glycol) methacrylate (PEGMA)‐based gelatin‐methacryloyl (GelMA)‐containing hydrogel that can be used to culture cells in 3D for at least 14 d. These gels are conveniently and quickly degraded via UV irradiation for 10 min to produce structured hydrogels of various geometries, sizes, and free‐standing cell‐laden hydrogel particles. These structures can be flexibly produced on demand. In particular, photodegradation can be temporarily delayed from photopolymerization, offering an alternative to hydrogel array production via photopolymerization with a photomask. The paper investigates the influences of hydrogel composition and swelling liquid on both its photodegradability and biocompatibility. Abstract : A novel biocompatible and inherently photodegradable gelatin‐methacryloyl (GelMA)‐containing hydrogel is polymerized to encapsulate normal human dermal fibroblasts for 14 d. An array of free‐standing cell‐laden hydrogel pads can be produced upon UV irradiation through the photomask.